2019
DOI: 10.1159/000496940
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Dietary Restraint Predicts Negative Treatment Outcomes after 12 Months in Children and Adolescents with Obesity Participating in a Lifestyle Intervention

Abstract: Objective: Current lifestyle interventions for children and adolescents with obesity often exclude patients with an eating pathology, leaving the impact of eating pathologies on treatment outcomes largely unconsidered. We investigated the predictive value of disordered eating symptoms on BMI z-score reduction in a sample of 111 German children and adolescents with overweight (90th percentile ≤ BMI < 97th percentile) and obesity (BMI > 97th percentile) aged 7–15 years in an outpatient lifestyle intervention pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 40 publications
(57 reference statements)
0
8
0
4
Order By: Relevance
“…These four studies also included one study that did find a significant association with weight loss at EOT, but the correlation was no longer significant at either follow‐up assessment (51). Additionally, the 10 studies with no significant associations included a study by Albayrak et al that found that higher baseline BE/LOC was associated with less weight loss, but results were not strong enough to be significant (36).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These four studies also included one study that did find a significant association with weight loss at EOT, but the correlation was no longer significant at either follow‐up assessment (51). Additionally, the 10 studies with no significant associations included a study by Albayrak et al that found that higher baseline BE/LOC was associated with less weight loss, but results were not strong enough to be significant (36).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies' samples had similar demographics. Twenty-four studies (82.8%) had majority-female samples, and only five had a majority of males (34)(35)(36)(37)(38). Additionally, race/ethnicity information on study samples was available for 18 studies.…”
Section: )mentioning
confidence: 99%
“…The majority of children and adolescents under supervised obesity treatment may have improvements or no change to ED risk profiles [72]. Higher baseline dietary restraint scores in obese children have been associated with increased rates of premature drop out from the intervention program compared to children who completed the program, independent of gender, age, and BMI z-score at baseline and mother's education level [73]. On the other hand, in a secondary analysis of an RCT focusing on changes in energy intake and diet quality during obesity treatment with post-treatment eating pathology in adolescents, there was no association between intensity of diet and EDs [74].…”
Section: Managementmentioning
confidence: 99%
“…In recent years, longitudinal research with adults has shown that increases in restraint over time may be associated with greater weight loss, but this relation has not been reproduced in studies among children or adolescents [ 11 , 65 ]. In a study involving a clinical sample of adolescents with overweight and obesity participating in a lifestyle intervention, higher baseline dietary restraint scores predicted a lower BMI z-score reduction across the 12-month study period [ 66 ]. In our study, the cross-lagged effects between dietary restraint in grade 3 and BMIz in grade 4 were non-significant, meaning dietary restraint was not associated with a change in weight (BMIz) in grade 4.…”
Section: Discussionmentioning
confidence: 99%